Spectral Distortions & Enhancements In Coherent Anti-Stokes Raman Scattering Hyperspectroscopy - Barlow, Aaron M. (Université d'Ottawa / University of Ottawa, 2015)
Coherent anti-Stokes Raman scattering microscopy is a versatile technique for label-free imaging and spectroscopy of systems of biophysical interest. Due to the coherent nature of the generated signals, CARS images and spectra can often be difficult to interpret. In this thesis, we document how distortions and enhancements can be produced in CARS hyperspectroscopy as a result of the instrument, geometrical optical effects, or unique molecular states, and discuss how these effects may be suppressed or exploited in various CARS applications.
Keywords: Spectroscopy; Nonlinear optics; Microscopy; Ultrafast optics